The Association Between Church Attendance and Psychological Health in Northern Ireland: A National Representative Survey Among Adults Allowing for Sex Differences and Denominational Difference - Lewis, Christopher Alan (Journal of religion and health, 2011)
This study extends previous research concerning the association between religion and psychological health in six ways: (1) by focusing clearly on religious attendance (church attendance); (2) by employing a robust measure of psychological distress (GHQ-12); (3) by studying a highly religious culture (Northern Ireland); (4) by taking sex differences into account (male or female); (5) by taking denominational differences into account (Catholic or Protestant); (6) and by obtaining a national representative sample (N = 4,281 adults aged 16 and above). Results from a 2 (sex) by 2 (denomination) ANCOVA demonstrated that Catholics recorded significantly lower levels of psychological health compared to Protestants, and that females showed significantly lower levels of psychological health compared to males. In addition, females reported higher frequency of religious service attendance than males, and Catholics reported higher attendance rates than Protestants. A significant positive association was found between frequency of religious attendance and GHQ-12 scores, and this association was moderated by sex and denomination. In conclusion, the results suggest that there may be sex and denominational differences in further understanding the relationship between frequency of religious attendance and psychological health.